A Review of Spinocerebellar Ataxias in Taiwan - Chia-Ju Lee; Chin-San Liu; Society for Neurological Rare Disorders-Taiwan (Acta Neurologica Taiwanica, 2025)
Spinocerebellar ataxias (SCAs) are a group of neurodegenerative diseases characterized by inherited progressive cerebellar ataxia with or without other associated features. The clinical presentations of these affected SCA patients are very heterogeneous. Genetic testing has been performed in the Taiwanese population to determine the prevalence of SCAs in Taiwan. In general, the diseases can be classified as those caused by tandem repeats and those with conventional mutations. Among the SCAs caused by tandem repeats, polyglutamine SCAs, including SCA1, SCA2, SCA3, SCA6, SCA7, and SCA17, are prevalent in Taiwan and worldwide. Other SCAs caused by non-CAG tandem repeats that have been investigated in Taiwan include SCA8, SCA12, SCA31, and SCA36. However, SCA12 and SCA31 seem either rare or absent in the Taiwanese population. On the other hand, there are SCAs caused by point mutations, duplications, insertions, and deletions. Taiwanese cases with SCAs related to ITPR1 gene mutations, SCA19/22, SCA28, SCA35, SCA47, and SCA48 have been studied and published. To generate a whole picture of SCAs in Taiwan, in this review, we summarized the prevalence of SCAs and described the characteristics of less common types of SCAs in Taiwanese patients.